A bibliometric study of Rubrics in self – assessment - Thị Huyền, Nguyễn; Hoan, Kieu Van; Thuy, Phạm Thu (International Journal of Scientific Research and Management (IJSRM), 2023)
Self-assessment in learning is an important skill that needs to be formed for students in the current teaching process. In order for students' self-assessment to take place regularly, it is necessary to have supportive assessment tools, in which rubric is considered an effective support tool in the self-assessment process. This article provides a bibliographic assessment of rubric's use in the learner's self-assessment process. Data were obtained from Scopus, where 69 databases related to the research issue from 2006 to 2021 were used.